The Influence of Job Recruitment, Work Shifts, and Occupational Safety and Health (K3) on the Performance of Cigarette Production Company Employees in Temanggung Regency - Selvi, Selvi; Santoso, Awan (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the influence of job recruitment, work shifts, and occupational safety and health (K3) on the performance of employees of Cigarette Production Companies in Temanggung Regency. The type of research used is descriptive quantitative, where the variables are measured using the Likert scale method. Data collection in this research was carried out by distributing questionnaires. The exact population size in this study is not known. The technique used in determining the sample in this study uses non-probability, choosing using purposive sampling, while determining the sample size in this study uses the Lameshow formula with a sample size of 100. Data processing is carried out using the SPSS application, the data analysis method used is multiple linear regression analysis with hypothesis testing t test and f test and testing the coefficient of determination. The results of this research show that simultaneously there is a significant influence of job recruitment, work shifts, and occupational safety and health (K3) on employee performance. Then, partially, the job recruitment assessment has a positive and significant effect on employee performance, work shifts have a significant positive effect on employee performance, and occupational safety and health (K3) has a significant positive effect on the performance of employees of Cigarette Production Companies in Temanggung Regency.